Apply Dots M-Health terhadap Peningkatan Minum Obat dan Kualitas Hidup Pasien Tuberkulosis Paru - Noviati, Elis; Sukmawati, Ima; Masru’ah, Iim Imas; Kurniawan, Rudi (Journal of Telenursing (JOTING), 2023)
This study aims to determine the effectiveness of Apply Dots M-Health in improving medication taking and quality of life. Pulmonary Tuberculosis Patients. This research method is quantitative research with a quasi-experimental one-group pretest-posttest design method. The results of the analysis using the Wilcoxon test obtained a p-value of 0.000 (ρ value < α (0.05)). In conclusion, there is an influence of DOTS M-Health on increasing medication taking and the quality of life of pulmonary tuberculosis patients. Keywords: DOTS M-Health, Medication Adherence, Quality of Life, Pulmonary Tuberculosis